5-n=-3n+5

Simple and best practice solution for 5-n=-3n+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-n=-3n+5 equation:


Simplifying
5 + -1n = -3n + 5

Reorder the terms:
5 + -1n = 5 + -3n

Add '-5' to each side of the equation.
5 + -5 + -1n = 5 + -5 + -3n

Combine like terms: 5 + -5 = 0
0 + -1n = 5 + -5 + -3n
-1n = 5 + -5 + -3n

Combine like terms: 5 + -5 = 0
-1n = 0 + -3n
-1n = -3n

Solving
-1n = -3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3n' to each side of the equation.
-1n + 3n = -3n + 3n

Combine like terms: -1n + 3n = 2n
2n = -3n + 3n

Combine like terms: -3n + 3n = 0
2n = 0

Divide each side by '2'.
n = 0

Simplifying
n = 0

See similar equations:

| 8x+5=2x+7 | | R=26x | | X*1+X= | | 26=15+v | | c/5=-11/6 | | -15x+11x-3=1-5(x+1) | | 3(y+6)=2y-2 | | 6=0x | | x+(x+1)=(x+2)-(x-1) | | 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 | | -17=v | | 3x+50i=18-5yi | | 45-11x=250 | | y-94=5(x-9) | | -4p-13p-p=-150 | | 4y-14=30 | | 14*30+b=-192 |

Equations solver categories